The Endorsement of Self-Regulated Learning Intercorporate with ELSA Speak AI to Boost Speaking Skill of Thai EFL Students - Aulia, Nazwa; Sagala, Rakhmat Wahyudin; Ginting, Pirman (Journal of English Language and Education, 2025)
The development of English-speaking skills among Thai EFL students remains challenging due to linguistic differences, rote-learning methods, and limited real-world practice. While technology-assisted learning is gaining attention, research rarely explores the integration of Self-Regulated Learning (SRL) with AI tools. This study examines the effectiveness of combining SRL with ELSA Speak AI to improve  speaking proficiency. Using Classroom Action Research (CAR), 30 sixth-grade students at Darul Muhmin Elementary School underwent a two-cycle intervention, with data collected through pre-tests, post-tests, interviews, and observations. Results show significant improvements in pronunciation, fluency, and confidence, with all students surpassing the minimum passing criteria. The study concludes that integrating SRL with AI fosters learner autonomy, engagement, and performance, demonstrating AI’s potential in EFL education.